Pengaruh Rasio Keuangan Terhadap Kinerja Keuangan (Studi Kasus Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Priode 2015-2019) - Serli Oktapiani; Servi Julian Kantari (Universitas Hamzanwadi, 2021)
Manufacturing companies listed on the Indonesia Stock Exchange (IDX) are the most important contributors of information for investors, especially regarding information on financial ratios to financial performance. This study aims to determine the effect of financial ratios on financial performance (a case study on a food and beverage sub-sector manufacturing company listed on the Indonesian stock exchange for the 2015-2019 period). This research is included in quantitative research and the population is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period, totaling 26 companies. With purposive sampling technique with certain criteria. The data analysis technique used classic assumption test, multiple linear regression analysis of panel data. The results of this study indicate that the current ratio (X1) partially has a positive and significant effect on the return on assets (Y) of food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Debt to equity ratio (X2) partially has a positive and insignificant effect on the return on assets (Y) of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2015-2019 period. Total asset turnover (X3) partially has a positive and insignificant effect on the return on assets (Y) of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2015-2019 period